Lung consolidation absorption time in 238 pediatric cases of mycoplasma pneumoniae pneumonia - Ou, YueXu; Cao, Jie; Qin, Bin; Luo, ZhengXiu; Du, HongQiang; Duan, YuanHui; Chen, FengHua; Zhou, JiWei; Li, YuanYuan; Zheng, YingLan; Gan, XiaoMing (Frontiers in Pediatrics, 2025)
ObjectiveTo investigate the lung consolidation absorption time and rate in children with mycoplasma pneumoniae pneumonia (MPP) and evaluate the impact of bronchoalveolar lavage (BAL) on absorption.MethodsChildren hospitalized with MPP and lung consolidation in Children's Hospital of Chongqing Medical University, between January 2018 and May 2024, were included for analysis. Patients were divided into BAL and non-BAL groups. Propensity score matching (PSM) was used to adjust for baseline differences between groups, and sub-group analyses were performed to assess the effect of BAL on lung consolidation absorption speed.ResultsAmong 238 children with MPP and lung consolidation, females slightly outnumbered males (129 vs. 109), with a mean age of approximately 5 years. Most children received azithromycin as the first-line treatment. Lung consolidation accounted for 4.48% (IQR: 2.61%–7.35%) of the total lung volume pre-treatment, with an absorption rate of 96.08% (IQR: 88.02%–98.95%) observed during follow-up at a median interval of 17 days (IQR: 15–21 days). The median absorption speed was 2.15 cc/day (IQR: 1.23–4.01 cc/day), with complete absorption occurring within 18.96 days (IQR: 16.14–23.33 days). Comparative analysis of the BAL and non-BAL groups revealed significant differences in fever duration, hs-CRP levels, consolidation-to-total lung volume ratio at admission, follow-up intervals, and consolidation absorption speed. Following 1:1 propensity score matching (PSM) to control for confounding factors, a statistically significant but small-to-medium effect persisted, with the median absorption rate remaining higher in the BAL group (2.13 cc/day) compared to the non-BAL group (1.60 cc/day).ConclusionsUsing CT scan to evaluate consolidation changes in children with Mycoplasma pneumonia, most children have 96% resolution within 2–3 weeks timeframe. Those who had a bronchoscopy may have a faster resolution rate but undertaking a flexible bronchoscopy under these circumstances is not a standard procedure in most settings.